ANALISIS HUKUM TERHADAP KETERLAMBATAN PEMBERITAHUAN PENGAMBILALIHAN SAHAM DITINJAU DARI HUKUM PERSAINGAN USAHA - Fernandes, Christo; Rr. Ani Wijayati; Paltiada Saragi (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
An acquisition is ithe taking iof iownership ior icontrol iof ithe ishares ior iassets iof ianother icompany, iand iin ithis ievent, ieither ithe itakeover icompany ior ithe iforeclosed icompany icontinues ito iexist ias ia iseparate ilegal ientity. iIf ithe itakeover iof ishares iof ia icompany iis idue ito ian iincrease iin ithe inumber iof iassets iand isales ivalue iafter ithe itakeover ithat imeets icertain icriteria iin iaccordance iwith ithe iprovisions iof iLaw iNo. i5 iof i1999 iand iother iderivative iregulations, iit imust ibe ireported ito ithe iBusiness iCompetition iSupervisory iCommission i(abbreviated iKPPU) ino ilater ithan i30 iworking idays ifrom ithe idate iof ithe itakeover iof ithe icompany’s ishares. Thus, ithe iauthor iconcludes ithat ithe iCommission iCouncil ihas imade ithe iright idecision. iThe iReported iParty ihas ibeen ilegally iproven iand iviolated iArticle i29 iof iLaw iNo. i5 iof i1999 iin iconjunction iwith iArticle i5 iof iPP iNo. i57 iof i2010. iBecause ieverything icontained iin ithe iarticle ihas ibeen ifulfilled, isuch ias ithe ifulfillment iof inon-acquisition iof ishares, ithe ivalue iof iassets iresulting ifrom ithe iacquisition iof ishares iexceeds ithe iminimum ilimit, inamely iexceeds iRp. i2,500,000,000,000.00 i(two itrillion ifive ihundred ibillion irupiah) iand ihas iexceeded ithe ieffective iperiod iof i30 idays.